Respuesta :

Answer:

[tex](x - 2)^{2} + (y - 3)^{2} = 36[/tex] is the equation of the circle

Step-by-step explanation:

[tex](x - h)^{2} + (y - k)^{2} = r^{2}[/tex]   where (h, k) is the center and r is the radius

In this case h = 2 and k = 3 and r = 6 (see below)

r adius =

[tex]\sqrt{(2 + 3)^{2} + (3 - 6)^{2} } \\= \sqrt{5^{2} + (-3)^{2} } \\= \sqrt{25 + 9\\}\\ = \sqrt{36} = 6[/tex]

Therefore,  [tex](x - 2)^{2} + (y - 3)^{2} = 36[/tex] is the equation of the circle

The point (- 3, 6) is on a circle with a center at (2, 3) So, the equation of the circle will be (x-2)^{2} +(y-3)^{2}= 6^{2}.

What is the general equation of a circle?

The general equation of a circle of radius represents all the points that lie on the circumference of the given circle.

The general equation of a circle is:

[tex]\rm (x-h)^{2} +(y-k)^{2}= r^{2}[/tex]

where (h, k) is the center and r is the radius

The point (- 3, 6) is on a circle with a center at (2, 3).

here, h = 2 and k = 3

[tex]\sqrt{(2+3)^{2} +(3-6)^{2}} \\\\\sqrt{5^2+3^2} \\\\\sqrt{36} \\\\6[/tex]

therefore, the radius is 6 units.

Now, the equation of a circle is:

[tex]\rm (x-h)^{2} +(y-k)^{2}= r^{2}[/tex]

[tex]\rm (x-2)^{2} +(y-3)^{2}= 6^{2}[/tex]

Learn more about the equation of a circle;

https://brainly.com/question/10618691